Juggling paid work and elderly care provision in Japan: Does a flexible work environment help family caregivers cope? - Yoko Niimi (Asian Development Bank Institute (ADBI), 2021)
Using unique data from a Japanese survey, this paper examines whether flexible work arrangements targeted specifically at workers with caregiving responsibilities under the Child Care and Family Care Leave Act help family caregivers reconcile paid work with care provision. The regression results suggest that access to caregiver leave, which allows family caregivers to take a continuous leave of up to 93 days, is found to be negatively and significantly associated with the probability of leaving one's job within one year of the onset of demand for parental care. This alleviating effect of access to caregiver leave remains robust even in the longer term and in a specification where we take into account the possible endogeneity of care provision to the labor supply decision. The findings of this paper thus suggest that the caregiver leave introduced pursuant to the Act in Japan helps meet the need of family caregivers to take a certain period of time off from work to make the necessary arrangements for accommodating the sudden and unexpected demand for elderly care in their daily lives.
Keywords: J14; J22; 330; elderly care; informal care; flexible work; labor supply; long-term care; Japan